The Effect of Fasting on Biochemical Balance in the Human Body: A Review - Attawi, Jamal A. ALJabbar (American Journal of Biomedicine and Pharmacy, 2025)
The topic of this review focus on the biochemical effects of fasting, with particular emphasis on metabolic responses that mobilize stored nutrients and preserve homeostasis in times of dearth. Primary adaptive responses include switching to fatty acid and amino acid metabolism (from glucose), the hormonally mediated ability to access additional energy for the brain, and stimulating cellular pathways that support improved energy utilization, stress resistance, and metabolic fitness. Although today’s sleep and feeding schedules can be erratic, when people are at least occasionally active then something might restore that metabolic balance. Prolonged fasting might combat the effects of modern life. Studies still delineate fasting’s effects, which depend on techniques and inter-individual differences, suggesting the requirement for more research.